Correção endovascular de pseudoaneurisma toracoabdominal em paciente com Doença de Behçet - Camargo, Paula Angeleli Bueno De [UNESP]; Bertanha, Matheus [UNESP]; Moura, Regina [UNESP]; Sobreira, Marcone Lima [UNESP]; Jaldin, Rodrigo Gibin [UNESP]; Yoshida, Ricardo De Alvarenga [UNESP]; Pimenta, Rafael Elias Farres [UNESP]; Yoshida, Winston Bonetti [UNESP] (FapUNIFESP (SciELO), 2015)
Behçet’s disease is an inflammatory disease characterized by recurrent oral and genital ulcers, uveitis and skin lesions. Arterial involvement is rare, but when present aneurysmal degeneration is more common than occlusive disease. This report describes the clinical case of a female patient who had been receiving treatment for Behçet’s disease for twenty years before presenting with abdominal pain that progressed for 2 months before suddenly worsening significantly. A CT scan revealed a thoracoabdominal pseudoaneurysm. She was successfully treated with endovascular repair.
Endovascular repair of a thoracoabdominal pseudoaneurysm in a patient with behçet’s disease
Keywords: Aortic aneurysm; Behçet’s disease; Dissecting aneurysm; Endovascular procedures